2021
DOI: 10.1111/1462-2920.15522
|View full text |Cite
|
Sign up to set email alerts
|

Sapwood and heartwood affect differentially bacterial and fungal community structure and successional dynamics duringQuercus petraeadecomposition

Abstract: In forests, bacteria and fungi are key players in wood degradation. Still, studies focusing on bacterial and fungal successions during the decomposition process depending on the wood types (i.e. sapwood and heartwood) remain scarce. This study aimed to understand the effect of wood type on the dynamics of microbial ecological guilds in wood decomposition. Using Illumina metabarcoding, bacterial and fungal communities were monitored every 3 months for 3 years from Quercus petraea wood discs placed on forest soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 100 publications
(138 reference statements)
0
11
0
Order By: Relevance
“…Dominance of bacteria belonging to Proteobacteria, Actinobacteria, Acidobacteria, and Bacteroidetes has been reported considering different wood species [5,[14][15][16][17]. If these phyla are representative of the bacterial communities colonizing deadwood, it is important to note that the related bacterial classes or genera differ according to the tree species, the decay stage, and the type of wood [5,[17][18][19][20]. While bacteria are poorly effective at decomposing dead wood compared to fungi, a few studies have shown that they are primarily involved in the decomposition of cellulose and pectin as well as in N fixation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dominance of bacteria belonging to Proteobacteria, Actinobacteria, Acidobacteria, and Bacteroidetes has been reported considering different wood species [5,[14][15][16][17]. If these phyla are representative of the bacterial communities colonizing deadwood, it is important to note that the related bacterial classes or genera differ according to the tree species, the decay stage, and the type of wood [5,[17][18][19][20]. While bacteria are poorly effective at decomposing dead wood compared to fungi, a few studies have shown that they are primarily involved in the decomposition of cellulose and pectin as well as in N fixation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Deadwood decomposition plays an essential role in forest ecosystems as it maintains the soil fertility and the physico-chemical balance of the biogeochemical cycles in these ecosystems (e.g., carbon (C) cycle, recycling of nitrogen (N), and micronutrients) [1]. This process is mainly performed by a succession of decomposers including insects, fungi, and bacteria that interact to progressively decompose and recycle the nutrients [2][3][4][5]. It also depends on abiotic environmental factors such as humidity, pH, or temperature that are also known to impact deadwood decomposition rates [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, substrate release and fungal biomass formation during wood decay may affect soil bacterial community through substrate acidification, fungal metabolites or degradable C source, etc. [ 26 28 ]. However, there is little documentation on the interactions between soil bacterial community and wood decomposition [ 29 ].…”
Section: Introductionmentioning
confidence: 99%